Urgensi Rekonstruksi Strafsoort dalam Hukum Pidana Indonesia - Ali Dahwir (Penerbit Goodwood, 2022)
Purpose: This study aims to identify and analyze problems regarding strafsort in Indonesian criminal law. Method: The research method used is normative legal research with descriptive analysis with a statutory approach and a philosophical approach. The data used in this study is secondary data in the form of legal materials. Legal materials consist of primary legal materials such as legislation and secondary legal materials such as reference books, research results and scientific journals. Result: The results of the study indicate that the strafsoort in Indonesian criminal law as stated in Article 10 of the Criminal Code when viewed in the development of the times is no longer appropriate. Such as imprisonment, criminal closure and fines. Therefore, the strafsoort in Indonesian criminal law is urgently reconstructed. Limitations: This research is limited to discussing strafsoort, therefore it is necessary to continue with a discussion of strafmaat and strafmodus in Indonesian criminal law. Contribution: This research is expected to be a recommendation in the formation of a new strafsoort by eliminating light prisons and adding social work penalties, as well as making peace as one of the reasons for eliminating punishments in particular.